Analysis of Sodium Benzoate Content in the Market Soft Beverages Using Uv-Vis Spectrophotometry Method - Akbar, Windi Hari; Pulungan, Ainil Fithri; Ridwanto, Ridwanto; Daulay, Anny Sartika (Pustaka Media Publishing, 2023)
Sodium benzoate is one of the preservatives that are permitted to be used in food and beverages. Research has been carried out with the aim of knowing that carbonated drinks contain the preservative sodium benzoate, knowing the amount of sodium benzoate in soft drinks and to find out the levels of sodium benzoate in soft drinks fulfilling the maximum usage requirements according to BPOM RI Head Regulation No. 36 of 2013. This study used the uv-vis spectrophotometry method. To determine the preservative content of sodium benzoate, a qualitative test was first carried out on the sample using the color reaction method and esterification test. To determine the levels using a UV-Vis spectrophotometer at a wavelength of 269 nm with ethanol p.a as a solvent. The results of the qualitative test using the color reaction method showed that the three samples of soft drinks positively contained the preservative sodium benzoate. To validate this, an esterification test was carried out on the three samples and they produced the smell of Ambon bananas which proved that the three samples positively contained sodium benzoate. For the quantitative test using the Uv-Vis spectrophotometry method at a wavelength of 269 nm using ethanol p.a as a solvent. The results of the analysis showed that the preservative content of sodium benzoate which was calculated for each sample was for a soft drink sample a: 244.93 ± 19.9349 mg/kg. Soft drinks b: 65.3 ± 0 mg/kg, soft drinks. Soft drinks c: 78.6 ± 13.1291 mg/kg. Based on these results, it can be concluded that the levels of sodium benzoate in samples A, B, and C met the standard requirements for maximum usage limits, namely not more than 600 mg/kg.